Evaluation of the Effect of Glass Fiber Inserts along with Bulk-Fill Composite on Fracture Resistance of Endodontically -Treated Premolar Teeth - Pourya Iraji; ghazaleh Ahmadi; Behnaz Esmaeili; Seyyed Sina Hashemi (Mashhad University of Medical Sciences, 2023)
Background: Compromised fracture resistance of endodontically treated premolars, is one of the most common dental problems. The aim of the present study was to investigate the effect of using fiberglass with bulk fill composite on fracture resistance of premolars. Materials and Methods: In this in vitro study, 60 healthy human premolar teeth were divided into 5 equal groups (n=12). The first group included healthy teeth without any cavity preparation. These teeth were considered as control group (negative control). In group 2, MOD cavity was prepared but not repaired and they were considered as positive control. Group 3, MOD cavity preparation was done similarly to group 2. The cavity was repaired with composite. Group 4: Preparation of the MOD cavity and etching and bonding steps were carried out in the same way as the previous group. A layer of composite was placed on the pulpal floor of the cavity and before curing, glass fiber was placed on the composite in the bucco-lingual direction and cured for 40 seconds. In group 5, cavity preparation and bonding were performed similar to the previous groups. Cavities were filled with composite up to a thickness of 4 mm. Then, glass fiber was extended on the composite and then the sample was cured for 40 seconds. The fracture resistance of the teeth was checked with a universal test device and finally the data was analyzed with SPSS software.Results: In the gingival fiber-reinforced group, the fracture toughness was significantly higher than the bulk composite-restored group (P=0.01), but this difference was not significant in the occlusal fiber group (P=0.870). No significant difference was observed between occlusal and gingival fiber groups. (P=0.38)Conclusion: Restoring endodontically treated premolars with bulk fill composite increases their fracture resistances, equal to an intact tooth, and using glass fibers in the gingival area of the cavity enhances its effect.